Beyond Alliances The Jewish Role in Reshaping the Racial Landscape of Southern California - Sanchez, George J. (Purdue University Press, 2011)
This volume focuses on the special role that Jews played in reshaping the racial landscape of southern California in the twentieth century. Rather than considering this issue in terms of broad analyses of organizations or communities, each contribution instead approaches it by examining the activity of a single Jewish individual, and how he or she navigated the social terrain of a changing southern California. In particular, this volume is one of the first to take seriously the unique racial/ethnic makeup of southern California for Jewish activism, with a particular focus on the relationship between Jews and Mexican Americans in the area around Los Angeles. The Jewish individuals who are this volume's subjects represent a wide spectrum of backgrounds and perspectives, ranging from an elected official to an activist lawyer, and from a local businessman to a Democratic Party organizer. The volume culminates with an interview with one of the most beloved of local university rabbis, who has been operating in the ever-changing environment of higher education in Los Angeles over the past thirty years. While its overall message is one of optimism, the volume does not shy away from taking on some of the more vexed issues in the scholarship of racial/ethnic interaction. While Jewish activism in shaping local civil rights is thoroughly discussed, the specific and unequal dynamics of power within the civil rights community is also analyzed. The changing relationship of Jews to "whiteness" in southern California during the late twentieth century, in both geographic and political terms, shapes many of these ongoing relationships. Finally, the volume provides a unique historical perspective on our understanding of contemporary Los Angeles in all its ethnic complexity, and specifically in thinking through the future of Jewish role in urban southern California.